Processed ship-based navigation data from the Tjornes Fracture Zone, offshore Northern Iceland, acquired during the R/V Bjarni Saemundsson expedition BSTFZB9 (2001) ... - Detrick, Robert (Interdisciplinary Earth Data Alliance (IEDA), 2009)
This data set was acquired with a ship-based navigation system during R/V Bjarni Saemundsson expedition BSTFZB9 conducted in 2001 (Chief Scientist: Dr. Robert Detrick). These data files are of ASCII MGDS:Nav format and include cleaned Primary Ship Navigation data. Data were acquired as part of the project: Pilot Study of the Tjornes Fracture Zone, offshore Northern Iceland, using High-Resolution Multi-channel Seismic Reflection Profiling and CHIRP Sonar, and funding was provided by NSF grant: OCE01-14357. ...